SOIL-WATER CHEMISTRY CHANGES AFTER SLASHING AND BURNING OF A "TERRA FIRME" FOREST PARCEL IN ALTA FLORESTA, MATO GROSSO, BRAZIL IN SOUTHERN AMAZON - Forti, M. C.; Gielow, R.; Carvalho, J. A.; Alvarado, E. C.; Sandberg, D. V.; Santos, J. C. (Geochimica Brasiliensis, 2012)